(untitled) (Physical Sciences and Technology, 2015)
One of the wide spread and economic methods of carbon nanomaterials (CNM) synthesis is an arc evaporation of graphite [1]. Products, formed in plasma due to the evaporation of graphite anode and containing CNM, are deposited on cathode and on reactor cold walls. Taken specimens are examined for different characteristics with little attention to physical-chemical processes, taking place at both on electrodes and in plasma. This work represents the authors’ opinion and offers a model (scheme) of CNM formation as a deposit on cathode, based on charged particles behavior in electromagnetic field patterns at the experimental temperature and pressure gradients along the arc axis.